Preparation and characterization of titania thin films for corrosion resistance enhancement - Chor, Phillip Yiu Fai. (2013)
This report will focus on aspect pertaining to surface modification of titanium to enhanced corrosion resistance. Unlike many other metals, titanium has the ability to withstand material corrosion when subjected to harsh conditions on the seabed. Nonetheless, every metal, including titanium has limiting properties and does not have zero tolerance towards corrosion. This report will present a detailed analysis and evaluation of the two methods, Thermal Oxidation and Anodisation. It is done by exploring effects of temperature and voltage towards corrosion resistance. By leveraging on the power of the chemical properties, this can lead to a new discovery of the optimum parameters, thus enhancing the durability of titanium.